2013
DOI: 10.1371/journal.pone.0076515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Orientation on Motor Imagery - Event Related Potentials Suggest Kinesthetic Motor Imagery to Solve the Hand Laterality Judgment Task

Abstract: Motor imagery (MI) refers to the process of imagining the execution of a specific motor action without actually producing an overt movement. Two forms of MI have been distinguished: visual MI and kinesthetic MI. To distinguish between these forms of MI we employed an event related potential (ERP) study to measure interference effects induced by hand orientation manipulations in a hand laterality judgement task. We hypothesized that this manipulation should only affect kinesthetic MI but not visual MI. The ERPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…Previous ERP studies have shown that mental rotation is accompanied by a negative-going amplitude modulation of the late-latency ERP components. [10][11][12] This modulation has been referred to as rotation-related negativity (RRN) and has been observed in several mental rotation studies. 10,11 Interestingly, RRN is more pronounced for outward rotated stimuli than for inward rotated stimuli.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Previous ERP studies have shown that mental rotation is accompanied by a negative-going amplitude modulation of the late-latency ERP components. [10][11][12] This modulation has been referred to as rotation-related negativity (RRN) and has been observed in several mental rotation studies. 10,11 Interestingly, RRN is more pronounced for outward rotated stimuli than for inward rotated stimuli.…”
mentioning
confidence: 91%
“…[10][11][12] This modulation has been referred to as rotation-related negativity (RRN) and has been observed in several mental rotation studies. 10,11 Interestingly, RRN is more pronounced for outward rotated stimuli than for inward rotated stimuli. 11,12 These findings suggest that RRN, similar to reaction time, is also modulated by biomechanical constraints.…”
mentioning
confidence: 91%
See 3 more Smart Citations